The Covid-19 Pandemic: Impacts on the Hospital Environment and Spatial Design - Nur Faridatull Syafinaz Ahmad Tajudin; Rohayah Che Amat (International Journal of Built Environment and Sustainability, 2022)
Covid-19 is the most significant pandemic that happened at the end of 2019, where the first confirmed case was reported in Wuhan, China. Given the high population and economic activities in cities, there are always possibilities for Covid-19 to spread widely. Hence, the impacts in the urban area are much bigger affected by this pandemic. The fact that existing hospital design raises concerns and questions among people across the globe regarding the hospital capacity and lack of flexibility to accommodate sudden surges of patients due to the Covid-19 pandemic. Previous studies showed that hospital spatial design and organization are crucial and impact users’ perceptions and experiences from multiple stakeholders. The scholars argue that the concept of restorative environment is rarely defined and some of the initiatives either focused on daily life in hospitals or broad terms about hospital architecture, layout, and interior design. The overview on the impact of Covid-19 towards hospital environment, hospital spatial design and its relationship through content analysis, and pilot survey as the groundwork are significant features to be discovered in this paper. This paper focuses on the existing hospital spatial design principles through theeffectiveness and efficiency of current hospital planning design during the pandemic. The result indicates that the empirical principles contribute to hospital planning and design quality and call for further research.